Nonlinear Dynamic Motivation-oriented Taxonomy of L2 Strategies based on Complex Dynamics Systems Theory - Bahari, Akbar (Journal of Language and Literature, 2019)
The need for a revisited framework of strategies in keeping with the nonlinear dynamic nature of motivational factors in L2 teaching led to the introduction of a taxonomy of nonlinear dynamic motivation-based strategies (NDMSs). This psycho-socio-cultural template suggests discovering dynamic motivational factors at individual level and integrating them into multiple parallel groups within a learner group instead of creating them which is a traditionally established function of motivational strategies to impose superficial cohesion on a learner group without catering for chaotic, emergent and dynamic individual motivational factors. Given the heterogeneity, dynamicity, and nonlinearity of the motivational factors at individual level, the first implication of the study is that NDMSs have the potential to activate identified motivational factors toward an adaptive and autonomous L2 motivation state regardless of their homogeneity or heterogeneity. Secondly, NDMSs have the potential to enable teachers to recruit the learning energy (i.e. motivation) from every member of the group via a dynamic and nonlinear set of motivational strategies instead of imposing a preset set of motivational strategies to all members of the group to elicit/facilitate/encourage equal performance from a motivationally heterogeneous learner group under the pretext of generating a cohesive learner group. Keywords: L2 motivation, nonlinear dynamic motivation-based strategies (NDMSs), complex dynamics systems theory (CDST)Â